Microalbuminuria as a Marker of Preclinical Diastolic Dysfunction in Newly Diagnosed and Never-Treated Essential Hypertension - Gajurel, RM; Sayami, A (Journal of Institute of Medicine Nepal, 2013)
Introduction: Hypertension (HTN) is a global public health problem with one fourth adults worldwide estimated to have high blood pressure (BP)1 The incidence of hypertension continues to increase in all developed and developing societies as the population grows older and more obese. The Framingham Study and other epidemiological surgeys have clearly defined HTN as an important cause of morbidity and mortality. The aim of this study was to determine the spot urine Microalbuminuria as a marker of preclinical cardiac structural and functional changes in the form of left ventricular diastolic dysfunction in newly diagnosed and never treated essential hypertensive subjects. Methods: A cross sectional study was used for those patients who were attended outpatient clinic of MCVTC with diagnosis of newly diagnosed and never treated hypertension over a period of October 2011 to November 2012. Results: A total of 130 essential hypertensive patients underwent for spot urine for microalbuminuria estimation and Echocardiography for evaluation of left ventricular diastolic function. Among 56 (43.1%) urine samples showed negative test [(Microalbuminuria -); ( UACR 30 mg/Gm)] and those 74 (56.9%) samples revealed positive test [(Microalbuminuria+); (UACR 30 to 300 mg/Gm)]. Patients with microalbuminuria positive was found to have more left ventricular diastolic dysfunction than those who were negative for Microalbuminuria. Conclusion: Microalbuminuria was found to have early preclinical marker of myocardial dysfunction in the form of left ventricular diastolic dysfunction in new and never treated essential hypertension. DOI: http://dx.doi.org/10.2126/joim.v35i1.8890 Journal of Institute of Medicine, April, 2013; 35:3-8